A clinical biomarker assay for the quantification of d3-creatinine and creatinine using LC–MS/MS. (March 2014) - Leonard, Michael; Dunn, John; Smith, Glenn
Background: Current methods to measure skeletal muscle mass are not practical in a clinical setting. Liquid chromatography–tandem mass spectrometry (LC–MS/MS) methods that measure the amount of urinary d3-creatinine enrichment after a single tracer dose of d3-creatine was developed.Results: The biomarkers d3-creatinine and creatinine were detected in human urine using LC–MS/MS. In this assay a surrogate analyte, d3-creatinine, was used to quantify endogenous creatinine. However, since endogenous concentrations of creatinine were orders of magnitude higher than d3-creatinine, the peak area of a less intense isotope of creatinine was acquired. A response factor is used to correct for using a less intense isotope multiple reaction monitoring transition.Conclusion: Novel LC–MS/MS assays were developed that quantify the biomarkers d3-creatinine, creatinine and d3-creatine in urine. This method allows the estimation of total body creatine pool size and subsequent calculation of muscle mass. This assay was originally validated as fit-for-purpose and was followed by full validation.